New insights into the stipitate hydnoid fungi Sarcodon, Hydnellum, and the formerly informally defined Neosarcodon, with emphasis on the edible species marketed in Southwest China - Di Wang; Hui Feng; Jie Zhou; Tian-Hai Liu; Zhi-Yuan Zhang; Ying-Yin Xu; Jie Tang; Wei-Hong Peng; Xiao-Lan He (IMA Fungus)
Abstract Sarcodon and Hydnellum are two ectomycorrhizal genera of important ecological and economic value in Southwest China, and they are common in the free markets in this region. It was estimated that more than 1,500 tonnes of them were sold as edible per year, but there was little information about the taxonomic placements of these edible mushrooms sold in the markets. Traditional concepts of the two genera have also been challenged recently, and circumscription of Sarcodon and the informally defined clade “Neosarcodon” remained unresolved. In the present study, specimens collected in the field and purchased from the markets in Southwest China were analyzed based on morphological characters and DNA sequences. Phylogeny of the traditional Sarcodon s. lat. and Hydnellum s. lat. was reconstructed from the combined internal transcribed spacer (ITS), nuclear large ribosomal subunit (nLSU) and RNA polymerase II second largest subunit (RPB2) dataset based on expanded samples to reevaluate the taxonomic placements of the two genera. In the present molecular analyses, four distinct clades were recovered and strongly supported: Hydnellum, Neosarcodon, Phellodon and Sarcodon. Neosarcodon is formally introduced as a generic name to include nine species previously placed in Sarcodon, and the delimitation of Sarcodon is revised based on phylogenetic and morphological studies. Phylogenetic analyses also revealed an unexpected species diversity (17 phylogenetic species) of Sarcodon and Hydnellum in the markets; nine phylogenetic species of Sarcodon and eight of Hydnellum were uncovered from the samples collected in the markets. Eight species were resolved in the traditional S. imbricatus complex, with S. imbricatus s.str. being the most common edible stipitate hydnoid fungal species. Three of the edible Hydnellum species (H. edulium, H. subalpinum, and H. subscabrosellum), and five separated from the S. imbricatus complex (Sarcodon flavidus, S. giganteus, S. neosquamosus, S. nigrosquamosus, and S. pseudoimbricatus), are described as new. Three new Chinese records (H. illudens, H. martioflavum, and H. versipelle), and the notable S. imbricatus and S. leucopus are also reported.